2013
DOI: 10.1007/s00383-013-3373-x
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic-assisted appendectomy in children: exteriorization of the appendix is a key component of a simple and cost-effective surgical technique

Abstract: TULAA, in which the appendix is exteriorized via a combination of open and laparoscopic techniques, is a safe and effective procedure for treating appendicitis in children. TULAA is a cost-effective treatment that provides excellent cosmetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 18 publications
1
45
1
Order By: Relevance
“…For example, a previous study reported the rate of conversion of LESS to conventional multiport appendectomy or the need for an additional transverse incision to range between 5 and 16.8% in pediatric cases. [13][14][15]. The transumbilical minimal incision approach does not require special equipment, or training such as that which is needed for laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 98%
“…For example, a previous study reported the rate of conversion of LESS to conventional multiport appendectomy or the need for an additional transverse incision to range between 5 and 16.8% in pediatric cases. [13][14][15]. The transumbilical minimal incision approach does not require special equipment, or training such as that which is needed for laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Four studies [3,[22][23][24] were excluded because they were subsequent follow-up questionnaire analyses of previously reported series. Finally, two [24,25], two [26,27], and three [28][29][30] studies were performed by the same author, respectively; therefore, we chose the most informative and recent article or merged information from multiple publications (different publications that used the same study sample). Eventually, fourteen studies [25,27,28,[31][32][33][34][35][36][37][38][39][40][41] matched the selection criteria and were suitable for the meta-analysis.…”
Section: Literature Searchmentioning
confidence: 99%
“…Eventually, fourteen studies [25,27,28,[31][32][33][34][35][36][37][38][39][40][41] matched the selection criteria and were suitable for the meta-analysis. These included 9 retrospective studies [25,27,31,34,35,37,[39][40][41], 3 prospective nonrandomized studies [28,32,36] and 2 prospective randomized studies [33,38], with a combined total of 2249 subjects. Out of these subjects, 744 (33%) underwent SILA and 1505 (67%) underwent CLA.…”
Section: Literature Searchmentioning
confidence: 99%
“…In this technique both parenteral and oral analgesics use was considerably lower in laparoscopic group due to decreased requirement by patients as shown by some other studies as well. 13,14 With regards to return to normal activities defined in our study as return to work show promising results for laparoscopic group of patients with mean time of 11.5+-3.1 days in laparoscopic patients and 16.1+-3.3 days in patients who underwent open appendectomy. Our results are in agreement to study by Helber el al 15 and other meta-analysis.…”
mentioning
confidence: 68%